Tetrahydroprotoberberine N-oxides from Chelidonium majus and their inhibitory effects on NO production in RAW 264.7 cells. (February 2021) - Le, Thi Phuong Linh; Lee, Jin Woo; Kim, Jun Gu; Han, Jae Sang; Kwon, Haeun; Lee, Dongho; Lee, Mi Kyeong; Hwang, Bang Yeon
Graphical abstract: Highlights: Two new tetrahydroprotoberberine N -oxides were isolated from Chelidonium majus . The absolute configurations of 1 and 2 were confirmed by calculated ECD method. Compounds 2, 6 -10, and 13 showed inhibitory effects on LPS-induced NO production. Abstract: Two new tetrahydroprotoberberine N -oxides, 7 R, 14 S - cis -tetrahydrocoptisine N -oxide (1 ) and 7 R, 14 R - trans -tetrahydrocoptisine N -oxide (2 ) along with fourteen known compounds (3 –16 ) were isolated from the aerial parts of Chelidonium majus . Their structures were elucidated by spectroscopic and spectrometric methods, such as 1D and 2D-NMR (HSQC, HMBC, NOESY) and HRESIMS. The absolute configurations of 1 and 2 were established by comparison of their experimental and calculated ECD data. All isolates were evaluated for their inhibitory effects on the nitric oxide production in LPS-induced RAW 264.7 macrophages, and compounds 2, 6 –10, 13, and 15 showed significant inhibitory effects with the IC50 values ranging from 1.1–31.9 μM.